A Model for Documenting Requirements Elicitation - Serna M., Edgar; Serna A., Alexei (Ingeniería, 2023)
Context: This work proposes a model to document the elicitation of requirements in the field of Requirements Engineering. Method: A systematic review of the literature was conducted to determine the validity and effectiveness of the existing models for documenting requirements elicitation. Results: By analyzing the results of this review, it was concluded that it is possible – and that is required – to take the best documented practices and add principles from logic, abstraction, and formal methods to them in order to structure a semi-formal model for documenting elicitation. Those currently proposed focus on techniques to collect information and pay little attention to documentation. In addition, these models are mainly based on natural language, which makes their interpretation difficult, and they generate re-processing in later stages of the life cycle due to ambiguities. Conclusions: This article describes a structured model, as well as its application and validation, by comparing it against five models found in the review.